Використання інформаційних технологій для бізнесу - Резниченко, Л.В.; Тімашов, О.О. (Економіко-математичне моделювання соціально-економічних систем, 2016)
The possibility of use of web-integration for the synchronized operation of the site, warehouse, accounting and other specialized programs for effective business interaction corporate resources or online stores with local information systems and any trade-accounts decisions in which changes in one link of the total systems affect others.